Conditions for forming future language teachers’ lexical competence in pandemic times - Bashkir, Olha; Kniaz, Hanna; Panchenko, Violetta; Bakhmat, Liudmyla; Sobchenko, Tetiana (My University, 2021)
Successful communication in English as a foreign language depends primarily on the amount of vocabulary learned, which ensures speech appropriateness in a particular communicative vocabulary in written and oral speech. Determining the range of students’ vocabulary, their word knowledge quality and ability to use target vocabulary at the control stage gives grounds to state the effectiveness of conditions for forming future language teachers’ lexical competence during the pandemic: using ICT and time-conditioned blended learning as a combination of traditional and distance learning.situation and adequate perception of information. The article reveals the conditions for forming future language teachers’ lexical com petence in Ukrainian higher pedagogical education institutions on the example of vocabulary denoting coronalogisms. The summative stage revealed students’ positive motivation for learning new vocabulary, while the formative one was aimed at expanding students’ range of vocabulary on a particular topic. The work was carried out in three stages: introducing new vocabulary; practicing and consolidating new material; using the target
Conditions for forming future language teachers’ lexical competence in pandemic times / O. Bashkir, H. Kniaz, V. Panchenko, T. Sobchenko, L. Bakhmat // Revista Amazonia Investiga, 2021. – Vol. 10. – Issue 43. – P. 72–82.
Keywords: лексична компетентність, короналогізми, іноземна мова, інформаційно-комунікативні технології, змішане навчання; lexical competence, coronalogisms, foreign language, information and communication technologies, blended learning; лексическая компетентность, короналогизмы, иностранный язык, информационно-коммуникативные технологии, обучение